2023
DOI: 10.13102/sociobiology.v70i2.7949
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vegetation Structure on Ant Diversity in Different Seasonal Periods in Impacted Fragments of Atlantic Forest

Abstract: The destruction of forest habitats generates extremely fragmented areas and changes in vegetation structure. That changes the characteristics of microhabitats and the availability of resources and affects the diversity of animal species such as ants, which are a large group with an important ecological role. As ants forage on trees and shrubs, the vegetation structure can affect the presence of these organisms. Abiotic factors such as seasonality can also influence the diversity of the ant community. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…Vegetation may drive the fine-scale spatial distribution of sympatric species by dictating the availability of resources at multiple scales ( Kubiak, Galiano & de Freitas, 2015 ), both spatial and temporal. Drawing on markedly different studies in the same forest type highlights the importance of vegetation; in Brazil’s Atlantic Forest, bat diet was best explained by landscape composition, particularly vegetation density ( Oelbaum et al, 2022 ), while in the same forest, the diversity of ants was explained by a combination of shrub leaf density and tree circumference ( Sampaio et al, 2023 ). Among macropods, Le Mar & Mcarthur (2005) showed that sympatric wallabies in Tasmania had similar food requirements and foraged in the same habitats by night, but that their selection of daytime refuges differed markedly, probably due to their contrasting predator avoidance strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation may drive the fine-scale spatial distribution of sympatric species by dictating the availability of resources at multiple scales ( Kubiak, Galiano & de Freitas, 2015 ), both spatial and temporal. Drawing on markedly different studies in the same forest type highlights the importance of vegetation; in Brazil’s Atlantic Forest, bat diet was best explained by landscape composition, particularly vegetation density ( Oelbaum et al, 2022 ), while in the same forest, the diversity of ants was explained by a combination of shrub leaf density and tree circumference ( Sampaio et al, 2023 ). Among macropods, Le Mar & Mcarthur (2005) showed that sympatric wallabies in Tasmania had similar food requirements and foraged in the same habitats by night, but that their selection of daytime refuges differed markedly, probably due to their contrasting predator avoidance strategies.…”
Section: Introductionmentioning
confidence: 99%